Cantidades hechizadas y silogísticas del sobresalto La secreta ciencia de José Lezama Lima - Vargas, Ómar, 1963- (Purdue studies in Romance literatures, 2021)
"Arguably the most important Cuban writer of the twentieth century, Jose Lezama Lima (1910-1976) is well-known as a poet, essayist, cultural promoter, and novelist, but not as a scientist. In fact, there is no evidence of any concrete relationship between him and any pure science discipline. How then it is possible to establish connections between Lezama's literary works and the disciplines of science? How are certain scientific discoveries and developments, such as the theory of relativity, quantum mechanics, modern logic, thermodynamics, or the big bang theory, embraced in the cultural imaginary of Cuba during the first half of the twentieth century? And finally, how do those scientific discoveries and developments inform Lezama's aesthetic production? Grounded in his disciplinary experience in both literary and mathematical studies, Vargas attempts to unearth the overlaps and connections between science and art, thus offering a new critical apparatus with which scholars can study Lezama's works. In this book, he provides a close reading of Lezama's narrative works, including his two novels-Paradiso and Oppiano Licario-as well as Lezama's essays, press articles, and interviews. The author also examines the catalog of Lezama's personal library, revealing that his poetics are based on an original and fascinating appropriation of concepts, problems, solutions, and rhetorical devices in science. Resumen en español: Probablemente el escritor cubano más importante del siglo XX, Jose Lezama Lima (1910-1976) es reconocido como poeta, ensayista, promotor cultural, y novelista, pero no por su relación con alguna disciplina de las ciencias puras. Cómo es posible entonces establecer algún tipo de asociación entre el pensamiento y la obra de Lezama con disciplinas científicas? Cómo se registran en el imaginario cultural de la Cuba de la primera mitad del siglo XX ciertos descubrimientos y desarrollos científicos como la teoría de la relatividad, la mecánica cuántica, la lógica moderna, la termodinámica, o la teoría del big bang? Y finalmente, quedan registrados esos descubrimientos y desarrollos científicos en la producción estetica de Lezama? Apoyado en la perspectiva que le brinda su formación academica tanto en matemáticas como en estudios literarios, Vargas intenta resolver estos interrogantes. Una lectura detallada de la obra narrativa del autor cubano, incluyendo sus dos novelas-Paradiso y Oppiano Licario-y de gran parte de sus ensayos, artículos de prensa y entrevistas concedidas por el, así como un examen cuidadoso de lo que sobrevivió de su biblioteca personal, muestran que la propuesta poetica de Lezama está sustentada sobre una fascinante y original apropiación de conceptos, problemas, soluciones, y características retóricas del quehacer científico"--